Southeast Research and Extension Center Agricultural Research 2025 (Kansas Agricultural Experiment Station Research Reports, 2025)
The 2025 Southeast Research and Extension Center Agricultural Research report includes research conducted in the areas of beef cattle management, cropping systems, and forage crops.
Keywords: cattle; corn; wheat; soybean; charcoal rot; bromegrass; fescue; endophyte